Effects of geochemical reactions on multi-phase flow in porous media during CO2 injection. (1st June 2020) - Seyyedi, Mojtaba; Giwelli, Ausama; White, Cameron; Esteban, Lionel; Verrall, Michael; Clennell, Ben
Abstract: Impacts of fluid-rock geochemical reactions occurring during CO2 injection into underground formations, including CO2 geosequestration, on porosity and single-phase permeability are well documented. However, their impacts on pore structure and multiphase flow behaviour of porous media and therefore on CO2 injectivity and residual trapping potential are yet unknown. We found that CO2 -saturated brine-rock interactions in a carbonate rock increased the grains roughness, increased the population of micro and macro pores and decreased the pore volume of medium size pores. These changes in pore structure led to a decrease in the sweep efficiency of the non-wetting phase (gas) during primary drainage. Furthermore, they led to an increase in the relative permeability of the non-wetting phase, a decrease in the relative permeability of the wetting phase (brine) and a reduction in the residual trapping potential of the non-wetting phase. The impacts of reactions on pore structure shifted the relative permeabilities cross point toward more water-wet condition. Finally, these reaction-induced pore structure changes caused a reduction in capillary pressure of the used carbonate rock. For CO2 underground injection applications, such changes in relative permeabilities, residual trapping potential of the non-wetting phase (CO2 ) and capillary pressure would reduce the CO2 storage capacity and increase the risk of CO2 leakage. Considering these fluid-rock reaction-induced changes is essential for accurate prediction/simulation of reservoir behaviour and risk analysis of the project.